Perception on effect of AYUSH treatment among patients with selected NCDs at life style diseases clinics from six states of India: Lessons learnt and way forward - T P Sherin Raj; Vijay Kumar Tiwari; Ramesh Gandotra (Wolters Kluwer Medknow Publications, 2023)
Introduction: The AYUSH system of medicine is effective in the case management of non-communicable diseases (NCDs). The Ministry of Health and Family Welfare launched a pilot program in 2016 integrating AYUSH with the National Programme for Prevention and Control of Cancer, Diabetes, Cardiovascular Diseases, and Stroke for community-based screening and management of NCDs. This study was done to assess the effectiveness of AYUSH treatment with Yoga practices in project districts in terms of the adoption of a healthy lifestyle besides relief from NCDs. Material and Methods: The study was conducted in six districts from six states, namely Bhilwara (Rajasthan), Surendranagar (Gujarat), Gaya (Bihar), Darjeeling (West Bengal), Krishna (Andhra Pradesh), and Lakhimpur-Kheri (Uttar Pradesh) with a total sample of 56 lifestyle disease Clinics and 1790 beneficiaries. Results: The results show that 75% of patients were currently doing yoga and 60%-80% of patients experienced various benefits of yoga. These benefits were relief from pain (82%), improvement in appetite (72%), reduction in weakness (72%), and sickness (71%). The study also found that after taking AYUSH treatment, overall 73% of patients reduced dosage of allopathic medicines, 52% had reduced side effects of allopathic medicines, 24% stopped allopathic medicine, and 50% got faster recovery. Conclusion: Low cost and fewer side effects are considered merits of AYUSH medicine that drive its acceptance in the community and could be prioritized under preventive care. The dual form of medicine is the new form emerging option to the existing modern medicine.